Pengaruh Model Project Based Learning Berbantuan Video Animasi Terhadap Hasil Belajar - Khatijah , Khatijah; Asriati, Nuraini; Adlika, Nur Meily (Jurnal Penelitian Pendidikan Geografi, 2026)
The ineffective learning process makes students feel bored so that learning outcomes are low. This study aims to determine the effect of the Project Based Learning (PjBL) model assisted by animated videos on the Hydrosphere material implemented in class X IIS Madrasah Aliyah Khulafaur Rasyidin. This study was conducted with a quantitative approach and utilized a quasi-experimental design as its research design. Research data were collected through pretests and post-tests in the form of multiple choices given to the control class X IIS A (male) and the experimental class X IIS B (female). The results showed that the average post-test score of the experimental class was 82.08, while the control class was 75.92. Based on the results of the t-test analysis, the t-count value was 2.40 which was greater than the t-table value at a significance level of 0.05. Thus, H₀ was rejected and Hₐ was accepted. This means that there is a difference in learning outcomes between students who learn using the PjBL model assisted by animated videos and students who learn using expository learning on the hydrosphere material in class X IIS Madrasah Aliyah Khulafaur Rasyidin. The implication is that the PjBL model assisted by animated videos can be recommended as an alternative learning strategy to improve student learning outcomes.